2010
DOI: 10.1002/cncr.25142
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization plus radiofrequency ablation therapy for early stage hepatocellular carcinoma

Abstract: the Tokai RFA Study Group BACKGROUND: Radiofrequency ablation (RFA) is becoming a well-known local therapy for hepatocellular carcinoma (HCC). Transcatheter arterial chemoembolization (TACE) is expected to enhance the effects of subsequent RFA by reducing arterial blood flow. However, the long-term efficacy of this combined therapy has not been elucidated. In this study, the survival rates of patients who received TACE combined with RFA (TACE þ RFA) were compared with those of patients treated surgically. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
4
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 41 publications
6
63
4
2
Order By: Relevance
“…38 However, the common procedure-related complications of the combined therapy such as hepatic infarction, biloma, abscess and hepatic arterial bleeding, reported by others, 27,31,34,39 did not occur in our study. In our study, posttreatment syndrome and transient increase in liver enzymes slightly were observed in all patients within 1 week after the treatment, which were comparable with those reported in other studies [8][9][10][11] ; these symptoms were usually self-limited and reversible without special treatment. Interestingly, an increase levels of serum creatinine and urea nitrogen slightly, indicating the renal function impaired, was observed in 7 patients (8.1%) at 1-5 days after the combined treatment.…”
Section: Discussionsupporting
confidence: 92%
“…38 However, the common procedure-related complications of the combined therapy such as hepatic infarction, biloma, abscess and hepatic arterial bleeding, reported by others, 27,31,34,39 did not occur in our study. In our study, posttreatment syndrome and transient increase in liver enzymes slightly were observed in all patients within 1 week after the treatment, which were comparable with those reported in other studies [8][9][10][11] ; these symptoms were usually self-limited and reversible without special treatment. Interestingly, an increase levels of serum creatinine and urea nitrogen slightly, indicating the renal function impaired, was observed in 7 patients (8.1%) at 1-5 days after the combined treatment.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, 1-year survival rate was 88% and 80% in RFA-TACE and TACE only respectively, which is comparable with previous studies showing 1-year survival rates at 93%, 98% and 100% in TACE-RFA treated groups. [19,23,26] The present study found that, 1-year recurrence-free survival rate was 56% and 24% in RFA-TACE and TACE respectively, which is in concordance with other studies reporting 1-year recurrence free survival rates of 74% and 64.5%. [22,26] Comparative studies have previously described TACE-RFA, a combined technique in which TACE was performed before RFA, and proved that it is much more better than mono-therapy, especially in medium and large sized HCC lesions.…”
Section: Discussionsupporting
confidence: 92%
“…[19,23,26] The present study found that, 1-year recurrence-free survival rate was 56% and 24% in RFA-TACE and TACE respectively, which is in concordance with other studies reporting 1-year recurrence free survival rates of 74% and 64.5%. [22,26] Comparative studies have previously described TACE-RFA, a combined technique in which TACE was performed before RFA, and proved that it is much more better than mono-therapy, especially in medium and large sized HCC lesions. Although it is different from the technique discussed in this study in which TACE was done after RFA (RFA-TACE), both have nearly the same results, with RFA-TACE presenting better responses with regards to CR and objective response than TACE-RFA and mono-therapy, especially in management of medium sized HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Kagawa and Kim reported their results comparing surgical resection and combined approach of TACE followed by RFA. They reported no differences in terms of overall survival, while recurrencefree survival was in favor of the surgical approach (p=0.01), whereas in the study from Kim and colleagues, no significant difference was found in terms of recurrence-free and overall survival between the two approaches (42,43). The two studies differ for the timing of RFA, which was scheduled on the day after TACE in the study by Kim et al, while in the study of Kagawa et al, it was performed within 2 months of TACE.…”
Section: Discussionmentioning
confidence: 83%
“…In 2010, Kagawa and colleagues reported the outcomes of a study involving 117 patients undergoing TACE followed by RFA within 2 months (62 patients) or surgery alone (55 patients) for early HCC (42). Inclusion criteria were no previous treatment for HCC, a single HCC <50 mm or up to three HCCs <30 mm, cirrhosis classified as CTP class A, no vascular invasion, and no extrahepatic metastasis, while exclusion criteria were ECOG performance status >2 and presence of an uncontrollable malignancy other than HCC.…”
Section: Ablative Therapies: Radiofrequency Ablation (Rfa) -Percutanementioning
confidence: 99%